Strategi Penguatan Penyuluhan Pertanian Terhadap Pemasaran Hasil Cabai Rawit Di Kecamatan Paguyaman Pantai Kabupaten Boalemo - Kadir, Liskawati; Rauf, Asda; Saleh, Yanti (Sam Ratulangi University, 2023)
The aims of this study were to identify internal and external factors in strengthening agricultural extension to the marketing of cayenne pepper and to formulate a strategy to strengthen agricultural extension to marketing cayenne pepper products in Paguyaman Pantai District, Boalemo Regency. The research method used is quantitative research in the form of a survey method. This research was conducted in Paguyaman Pantai District, Boalemo Regency in December 2022 to January 2023. The data analysis used was quantitative descriptive analysis and SWOT analysis. The results of the study show that: 1) Internal and external factors that influence the strategy of strengthening agricultural extension to the marketing of cayenne pepper in Paguyaman Pantai District, Boalemo Regency consist of: internal factors, namely the land that is owned by themselves, the experience of farmers in developing cayenne pepper farming, the existence of directives from extension agents to farmers in developing cayenne pepper farming, cayenne pepper is included in the leading commodity and there are suitable soil conditions, cayenne pepper production is not optimal, selling price for cayenne pepper is unstable, cayenne pepper marketing is uncertain, cayenne pepper commodity is easily damaged and rotten, external factors, namely the support of the local government regarding cayenne pepper farming, the exhibition of horticultural agricultural products, the availability of seeds and fertilizers, the the existence of supporting facilities and infrastructure, the existence of b road cayenne pepper distribution channels, the increasing demand for cayenne pepper, Unstable weather conditions, prices for seeds and fertilizers that are increasingly difficult to reach by farmers, pests and diseases that attack, cayenne pepper prices fluctuate, competitors, limited land. 2) Strategy for strengthening agricultural extension to marketing cayenne pepper products in Paguyaman Pantai District, Boalemo Regency, which is in quadrant I supporting an aggressive strategy or SO (Strength-Opportunities) by using the strengths and opportunities they have to minimize existing weaknesses and threats so as to achieve improvement.